How big is China’s digital economy? - Garcìa-Herrero, Alicia; Xu, Jianwei (Brussels, 2018)
"The rise of influential Chinese digital giants, including Baidu, Alibaba, Tencent and Xiaomi has shown the world that China is a global leader in digital innovation and it is not surprising that China has started to influence the global digital market. But is China exploiting its full potential in this area? To answer this question, the authors assess how big China’s digital economy is relative to the rest of its economy, and how China performs compared to the rest of the world."